Hubungan Pengetahuan dan Sikap Keluarga dengan Upaya Pencegahan Demam Berdarah Dengue (DBD) di Wilayah Kerja Puskesmas Air Dingin - Ritu Santia Putri; Nurhaida (Jurnal Kesehatan Lentera 'Aisyiyah, 2025)
Dengue Hemorrhagic Fever (DHF) is an infectious disease that remains a public health problem in Indonesia, including in the Air Dingin Community Health Center (Puskesmas Air Dingin) area. According to data from the Padang City Health Office, of the 24 existing community health centers, Air Dingin Puskesmas recorded the highest number of DHF cases, with 38% of cases. Initial survey results indicate that 7 out of 10 residents still lack understanding of disease prevention efforts, necessitating increased public knowledge and awareness regarding DHF prevention. This type of research is quantitative with a cross- sectional design, conducted on July 17–28, 2025. The study population was heads of families or family members domiciled in the Air Dingin Community Health Center Working Area. Samples were taken using the proportional stratified random sampling technique. Data analysis was carried out using univariate and bivariate methods. The results of the study showed good knowledge (37.4%), good attitudes (88.9%), and good prevention efforts (62.6%). A p-value of 0.000 < 0.05 indicates a significant relationship between family knowledge and attitudes and dengue fever prevention efforts. It is hoped that the Community Health Center will strengthen community outreach and empowerment so that awareness and participation in eradicating mosquito nests will increase.